2005
DOI: 10.1016/j.bbrc.2005.04.093
|View full text |Cite
|
Sign up to set email alerts
|

The uncovering of a novel regulatory mechanism for PLD2: Formation of a ternary complex with protein tyrosine phosphatase PTP1B and growth factor receptor-bound protein GRB2

Abstract: The regulation of PLD2 activation is poorly understood at present. Transient transfection of COS-7 with a mycPLD2 construct results in elevated levels of PLD2 enzymatic activity and tyrosyl phosphorylation. To investigate whether this phosphorylation affects PLD2 enzymatic activity, anti-myc immunoprecipitates were treated with recombinant protein tyrosine phosphatase PTP1B. Surprisingly, lipase activity and PY levels both increased over a range of PTP1B concentrations. These increases occurred in parallel to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…As indicated previously by our laboratory, PLD2 exists as a complex with Grb2 and PTP1b (Horn et al, 2005). Here, we report that PLD2 residues Y 169 and Y 179 directly bind Grb2 and recruit Sos in vivo.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…As indicated previously by our laboratory, PLD2 exists as a complex with Grb2 and PTP1b (Horn et al, 2005). Here, we report that PLD2 residues Y 169 and Y 179 directly bind Grb2 and recruit Sos in vivo.…”
Section: Introductionsupporting
confidence: 79%
“…The data presented here identify for the first time two neighboring tyrosines, Y 169 and Y 179 , in the PLD2 molecule as being essential for the Grb2/PLD2 interaction that our laboratory has described recently (Horn et al, 2005). The amino acids Y 169 and Y 179 in PLD2 are expressed within the context of perfect matches for SH2-mediated Grb2 interaction (pYxNx) (Songyang et al, 1993(Songyang et al, , 1994.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Overexpression of XGrb2 SiL did not result in acute upregulation of endogenous Grb2 mRNA due to transfection artifacts, demonstrating that endogenous Grb2 silencing can be rescued at the protein level. Our laboratory has previously shown that Grb2, as part of a Shc-Grb2-SOS complex is essential for the signaling of the phospholipase D2 (PLD2) isoform through the SOS-RAS-RAF-MAPKK-MAPK signaling cascade and eventual effect on DNA synthesis and cell growth [12,13]. Efficient signaling requires association of the lipase with Grb2 through an identified residue, (as the Src homology 'SH' region-2 binds to phosphorylated tyrosine residues).…”
Section: Discussionmentioning
confidence: 99%
“…COS7 were routinely transfected following lipofectamine-based procedures as described in detail elsewhere [45]. RAW cells were nucleofected with the Amaxa-based (Gaithersburg, MD) electroporation cuvette with 2×10 6 cells/100 µl in nucleofector solution V. Cells were "zapped" in program D-32 (as per the manufacturer's instructions) after which they were resuspended in 1 ml DMEM + 20% FBS and immediately plated into six-well plates.…”
Section: Transient Transfection Of Cos7 or Raw-2674 Cellsmentioning
confidence: 99%